Haze pollution: regulating corporate responsibility and liabilities under Environmental Law in Malaysia - Mustafa, Maizatun; Ariffin, Mariani; Rusli, Mohd Hazmi; Mat Seman, Nurulnabila Hanis (Fakulti Undang-undang, Universiti Teknologi MARA, 2019)
In the past 30 years Malaysia has been enjoying significant economic growth that arises mainly from industrialization. However, the expansion of economic sector and industrial process have inevitably jeopardised environmental quality and contributed towards degrading air quality and occurrance of haze. Consequences of economic activities on the environment have already been acknowledged and various measures have been introduced to regulate such activities. However, while the main focus of controlling air pollution has always been on regulating emission discharge, one important but less developed aspects of such control is pertaining to corporate environmental duties as well as liabilities. The notion of corporate’s legal duty to meet general environmental protection obligations is something relatively new to Malaysia but progressing. This can be seen from the introduction of strategies within environmental law that invoke either self-regulation or shared responsibility between government and industry relating to environmental protection and pollution control, and in imposing criminal sanction upon corporation that commit environmental offences. In light of the fact that sources of haze pollution can be attributed to “growth-related” activities as manifested by the rise in the emission of air pollution which causes haze, the objectives of this article are to examine the role of domestic law in requiring corporations to fulfill their environmental responsibility, and in imposing criminal liabilties for haze related offences. While the extent of company’s duties as well as accountability can be found within the provisions of domestic environmental law, the article also seeks to find out to what extent similar provision can be applied in relation to transboundary haze pollution which has been affecting Malaysia for many years. This paper concludes that understanding of the scope and limitation of domestic law is pertinent in facilitating Malaysia’s next cause of action towards enhancing the regulation of corporate environmental responsibility as well as liabilities associated with domestic and transboundary haze pollution, and in promoting environmental sustainability.